Fuzzy speciallist system application to the evaluation of a customer satisfaction research in an industry of vehicle parts - Campos de Aguiar, Dimas; Pamplona Salomon, Valério Antônio (Revista Ciências Exatas, 2009)
This work approaches the results measurement of a customer satisfaction research in an industry of vehicle parts located at Vale do Paraíba. This research was carried through in five assembly plants that are customers of this organization, with three concentration departments: Quality; Logistic and Commercial. The analysis of the results was made with the application of the specialist system diffuse through the modeling of specialist systems with fuzzy sets.